A new species of Bittacus Latreille (Mecoptera: Bittacidae) from the Andean-Amazonian foothills, Caquetá, Colombia - Machado, Renato Jose Pires; Higinio, María Fernanda Bermúdez; Guevara, Yennifer Andrea Carreño; Ramos-Pastrana, Yardany (Zootaxa, 2022)
A new hangingfly species, Bittacus rafaeli sp. nov. (Mecoptera: Bittacidae), is herein described and illustrated, based on two specimens from the municipality of El Doncello, Caquetá, Colombia. This is only the ninth Mecoptera species recorded from the country and the twenty-eighth species of Bittacus from South America. A distribution map of the Bittacus species from Colombia is presented.